A Photoelectrochemical Sensor for Firstly the Detection of Amlodipine Besylate Based on an MnC4Pc Coated ZnO Composite Materials. Issue 1 (19th May 2022) - Li, Xueying; Li, Xiaokun; Feng, Suxiang
Abstract: In this study, tetracarboxylic manganese phthalocyanine coated nano‐zinc oxide (MnC4 Pc‐ZnO) composite material was prepared by in‐situ growth method and modified with indium tin oxide (ITO) glass electrode to construct a photoelectrochemical (PEC) sensor. A PEC sensor for the determination of amlodipine besylate (AB) was developed for the first time based on the principle of precipitation reaction between heavy metal ions and dihydropyridine and the recombination suppression effect of the material. The morphology and optical properties of the MnC4 Pc‐ZnO composites were characterized by scanning electron microscopy (SEM) and ultraviolet‐visible diffuse reflectance spectroscopy (UV‐vis DRS). Chronoamperometry (i‐t) and electrochemical impedance spectroscopy (EIS) were used to study the PEC behavior of ITO electrodes modified by MnC4 Pc‐ZnO composite material. The study found that the MnC4 Pc‐ZnO composite material has a good photocurrent response to AB, and there was a good linear relationship between the concentration range of 75 nM‐250 μM, the linear equation was I (μA)=−5.2×10 −8 ×lg C +3.2×10 −8 (r=0.9947), a limit of detection (LOD) of 20 nM. In addition, MnC4 Pc‐ZnO/ITO also has good selectivity and stability. The PEC sensor detects amlodipine besylate tablets, amlodipine besylate dispersible tablets, and biological samples, with standard addition recovery rates of 96.11 % and 103.96 %, respectively. The determination result has good accuracy, and the PEC sensor provides a new method for detecting AB. Abstract :